Women in the Shadow of Self Racism: A Phenomenological Study of Women Using Instagram - Suhada, Djilzaran Nurul; Demartoto, Argyo; Sunesti, Yuyun (Interdisciplinary Social Studies, 2022)
Social media in this day and age, developed not only for communication between users. Instagram, for example, is one of the social media where users can express themselves through pictures and short videos. Instagram is also a social media where users can find new professions that we can call influencers or beauty influencers. In this research, it will be proven that women Instagram users will be trapped in what is called self-racism, a situation that always makes someone dislike themselves so much and try to be someone they idolize on Instagram. This research was conducted on 4 female informants who are different in terms of ethnicity, these ethnicities include Arab, Batak, Chinese and Papuan ethnicities and these ethnicities can be regarded as a large ethnicity in Indonesia. This research was also carried out using qualitative research methods with a phenomenological approach and also using analytical theory from Jean Paul Baudrillard. Women who use Instagram will be racist to themselves by dressing in style, applying makeup in a similar way, and even altering their bodies to make them thinner in order to resemble their idols on social media.